From Financial Inclusion to Financial Vulnerability: The Role of Debt Pressure and Risk Awareness Among MSME Digital Lending Users - Carolina Ety Widjayanti; Wiwiek Rabiatul Adawiyah; Sudarto (Fundamental and Applied Management Journal, 2026)
The rapid growth of digital lending has expanded financial inclusion among micro, small, and medium enterprises (MSMEs) by providing faster and more flexible access to financing. However, excessive reliance on digital lending may also increase financial vulnerability through rising repayment burdens and debt pressure. This study examines the effect of digital lending on MSME financial vulnerability, the mediating role of debt pressure, and the moderating role of risk awareness. Using a cross-sectional survey design, data were collected from 175 MSME owners who had experience using digital lending services. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that digital lending has a positive and significant effect on debt pressure, while debt pressure significantly increases financial vulnerability. The direct effect of digital lending on financial vulnerability remains significant, and the bootstrapped indirect effect through debt pressure is also significant (β = -0.247, p = 0.009), confirming the presence of partial mediation. Furthermore, risk awareness significantly moderates the relationship between debt pressure and financial vulnerability, weakening the negative impact of debt pressure on MSME financial conditions. These findings highlight the paradox of digital financial inclusion, in which easier access to financing may simultaneously create financial pressure and vulnerability when not accompanied by adequate risk awareness. The study contributes to the behavioral finance and financial vulnerability literature by integrating mediation and moderation mechanisms within a single framework and offers practical implications for MSME owners, fintech providers, and regulators in promoting responsible digital lending practices.